Reconsidering Elitist Duality: Persistent Tension in the Turkish–Egyptian Relations. (20th September 2016) - Magued, Shaimaa
Abstract: Since the Muslim Brotherhood's ouster in July 3, 2013, tension has escalated between Turkey and Egypt and gained media attention as an unprecedented incident in bilateral relations. However, disagreement has characterized bilateral relations since the declaration of the Egyptian Republic and the launch of diplomatic relations with Turkey in the 1950s. By tracking the history of both countries' bilateral relations, this study contends that, according to the elitist duality thesis, Turkish – Egyptian relations were an exception to the Turkish – Arab relations, as they were not influenced by the ruling elite. It argues that regardless of the ruling elite identity, tension has disrupted the normal course of relations. By relying on extensive interviews conducted with members of the Justice and Development Party, and academicians and staff members in the Turkish ministries of economy and foreign affairs, the study analyzes the unaddressed tension in the Turkish – Egyptian relations since the 1950s until 2013 and provides policy recommendations to improve bilateral relations.